Pragmatic discourse analysis of speakers’ dialogue in Korean language among university students - Lee, Ji Soo (2021)
The purpose of this dissertation is to identify the speakers’ (or writers’) intended implicit meaning in dialogue, in the form of student-generated written texts to emulate oral discourse which is in two dimensions: pragmalinguistics and sociopragmatics, which Malaysian Korean learners should consider in context to reduce the gap between ‘what is said’ and ‘what is communicated’ in a discourse situation. Thus, the first objective was to identify the speakers’ implicit meaning through presupposition, implicature, and deixis. The second objective was to discuss the function of cultural schemata and differences in values to enable the interpretation of the speakers’ intended implicit meaning of sentences. The third objective was to analyze the implicit meaning of politeness in Korean dialogue to discern the meaning of politeness or impoliteness expressed by the speakers’ intention in the context. 100 dialogue samples from 50 university students at Universiti Putra Malaysia were collected and analyzed using Yule’s (1996) pragmatics model and Hur’s (2012) model for Korean politeness. Findings revealed that there are many linguistic forms, cultural factors, and social variables that are involved in the contextual meaning of the speakers’ utterances which affect pragmatic failure among Malaysian Korean learners. Based on these findings, it can be concluded that pragmatic discourse analysis is an efficient method to analyze Korean discourse for narrowing the gap between ‘what is said’ and ‘what is communicated’ in order to prevent pragmatic failures for successful communication among students at Universiti Putra Malaysia.